2017
DOI: 10.4103/0970-9371.197579
|View full text |Cite
|
Sign up to set email alerts
|

Role of morphometry in the cytological differentiation of benign and malignant thyroid lesions

Abstract: Context:Thyroid nodules represent a common problem, with an estimated prevalence of 4–7%. Although fine needle aspiration cytology (FNAC) has been accepted as a first line diagnostic test, the rate of false negative reports of malignancy is still high. Nuclear morphometry is the measurement of nuclear parameters by image analysis. Image analysis can merge the advantages of morphologic interpretation with those of quantitative data.Aims:To evaluate the nuclear morphometric parameters in fine needle aspirates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…In general, virtually all studies have found statistically significant differences in nuclear area (and many other nuclear features evaluated) between benign and PTC nuclei (Table ) . Many have reported sufficient overlap to limit the utility in clinical practice, but others have found that nuclear area, alone or in combination with other morphometric features, can achieve accuracy of 70% or greater . The current study found relatively good distinction by nuclear area, albeit with limited overlap in cases with indefinite qualitative cytologic interpretations.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…In general, virtually all studies have found statistically significant differences in nuclear area (and many other nuclear features evaluated) between benign and PTC nuclei (Table ) . Many have reported sufficient overlap to limit the utility in clinical practice, but others have found that nuclear area, alone or in combination with other morphometric features, can achieve accuracy of 70% or greater . The current study found relatively good distinction by nuclear area, albeit with limited overlap in cases with indefinite qualitative cytologic interpretations.…”
Section: Discussionsupporting
confidence: 46%
“…However, nearly all studies have used nuclear area as one of their indicators, and several have used some sort of measure of roundness/ovalness. In general, virtually all studies have found statistically significant differences in nuclear area (and many other nuclear features evaluated) between benign and PTC nuclei (Table ) . Many have reported sufficient overlap to limit the utility in clinical practice, but others have found that nuclear area, alone or in combination with other morphometric features, can achieve accuracy of 70% or greater .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations